Longitudinal within- and between-person associations of substance use, social influences, and loneliness among adolescents and emerging adults who use drugs. (4th July 2022) - Bonar, Erin E.; Walton, Maureen A.; Carter, Patrick M.; Lin, Lewei A.; Coughlin, Lara N.; Goldstick, Jason E.
Abstract: Loneliness is a public health problem causing morbidity and mortality. Individuals with substance use problems are often lonelier than the general population. We evaluate the longitudinal associations between social influences, substance use, and loneliness among adolescents and young adults recruited from an urban Emergency Department (ED). We use secondary data from a natural history study of N = 599 youth (ages 14–24) who used drugs at baseline and completed biannual assessments for 24 months; 58% presented to the ED for an assault-related injury and a comparison group comprised 42% presenting for other reasons. Measures assessed cannabis use, alcohol use, and loneliness. Using GEE models, we evaluated the relationships between social influences (peers, parents), substance use, and loneliness via longitudinal data, de-coupling within- and between-person effects. Men reported lower loneliness over time. At the between-person level, individuals with greater alcohol and cannabis use severity and negative peer influences had greater loneliness; positive parental influences were associated with less loneliness. At the within-person level, greater alcohol use severity, negative peer influences, and parental substance use corresponded to increases in loneliness; positive parental influences corresponded to decreases in loneliness. Youth with more severe alcohol and cannabis use had greater loneliness over time. Within individuals, peer and parental social influences were particularly salient markers of loneliness. An ED visit provides an opportunity for linkage to personalized, supportive interventions to curtail negative outcomes of substance use and loneliness.